Endovascular Management of Post-Dissection Thoracoabdominal Aortic Aneurysms After the Acute Phase: Mid-Term Outcomes of F/BEVAR - Victor Bilman; Natalie Noam; Lihi Cohen; Moshe Halak; Daniel Silverberg (Journal of Clinical Medicine, 2026)
Background/Objectives: Not all patients with acute aortic dissection undergo endovascular repair at initial presentation, and surgical or endovascular interventions are often required for late aneurysmal degeneration. This study aims to report the mid-term outcomes of fenestrated/branched endovascular aortic repair (F/BEVAR) of post-dissection thoracoabdominal aortic aneurysms (PDTAAAs) and to compare them with the outcomes of patients treated for degenerative thoracoabdominal aortic aneurysms (DTAAAs). Methods: A single-center retrospective analysis was performed, including all consecutive patients who underwent F/BEVAR for TAAAs between 2020 and 2025. A total of 95 patients were identified (18 PDTAAAs and 77 DTAAAs). All patients underwent elective repair; ruptured TAAAs were excluded. A comparative analysis was performed between the PDTAAA and DTAAA groups. Results: During the study period, a total of 95 patients who underwent F/BEVAR for TAAAs (mean age 66 ± 10 years, males n = 68, 72%) were identified. Eighteen patients (males n = 14, 78%) underwent F/BEVAR for PDTAAAs, and 77 (males n = 54, 78%) for DTAAAs. The patients in the post-dissection group were younger (62 ± 14 years vs. 70 ± 8 years; p < 0.01). Aneurysms in the PDTAAA group more commonly involved the proximal descending aorta (Crawford type 1 and 2 TAAA: n = 12/18, 67% vs. n = 14/77, 18%; p < 0.01). Aortic arch debranching procedures were performed at a higher rate in the PDTAAA group (8/18, 44% vs. 8/77, 10%; p < 0.01). No mortality within 30 days occurred in the post-dissection group but it did occur in 2/77 (3%) patients in the degenerative group (p = 0.68). Mean follow-up was 31 months (range: 3–121 months). Freedom from reintervention was similar between the two groups (55% vs. 60%, non-significant). Overall survival was significantly higher in the PDTAAA group (90% vs. 60%; p = 0.021). Conclusions: F/BEVAR is technically feasible for PDTAAAs. Technical success and reintervention rates do not differ between post-dissection and degenerative TAAAs; however, overall survival is higher in patients with post-dissection aneurysms.